An Analysis of Trust Levels of Teachers Who Teach in Primary Schools with Respect of Some Variables - Cumali TEKİN (Gaziantep University Journal of Social Sciences, 2014)
The purpose of this study is to determine whether or not trust levels of the teachers who teach in the primary schools where they teach differ in relation to some varriables. The independent variables of the study are theachers’ages, length of their teaching in the schools, length of their teaching in the Ministry of Education, subject speciality, level of training and types of faculties they graduated. The universe of this survey type study consisited of the teachers working in the 2011-2012 education year in the state primary schools located in the Şahinbey Town of Gaziantep. The study covered a represantative random sample of 517 teachers from 17 primary schools included in the universe of the study. The Likert-type scale of trust in schools developed by Polat (2007) was used to determine the trust levels of the theachers teaching in the primary schools. According to the findings of the study, average trust level of the theachers in their schools was found to be at “high” level. Stastical analysis showed that there was no significant difference between the teachers’ confidence levels in their schools in terms of independent variables except for the age variable